Risk of Escherichia coli O157:H7 transmission linked to the consumption of raw milk - Lye, Y. L.; L., Afsah-Hejri; Chang, W.S.; Loo, YY; Puspanadan, S; Kuan, CH; Goh, SG; Shahril, N; ., Rukayadi; Khatib, Alfi; John, YHT; ., Nishibuchi; et al. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
E. coli O157:H7 is associated with life threatening diseases such as hemorrhagic colitis (HC), hemolytic uremic syndrome (HUS) and thrombotic thrombocytopenic purpura (TTP). Raw milk is considered a high risk food as it is highly nutritious and serves as an ideal medium for bacterial growth. The aim of this study was to investigate the prevalence of E. coli O157:H7 in raw cow, goat and buffalo milk samples. MPN-PCR method targeting the major virulence rfbE gene and fliCH7 gene of E. coli O157:H7 was used. Total of 177 raw milk samples were collected from local dairy farms in the state of Selangor, Malaysia. The highest prevalence of E. coli O157:H7 was found in raw cow milk (8.75%) followed by raw goat milk (7.32%) and raw buffalo milk (1.79%). The estimated quantity of E. coli O157:H7 in raw cow, goat and buffalo milk ranged from <30 MPN/g to 120 MPN/g. In raw cow and goat milk samples examined contain E. coli O157:H7 microbial load ranged from 30 to 120 MPN/g and 30 to 36 MPN/g, respectively. E. coli O157:H7 microbial load in buffalo milk samples was found to be the lowest, only 30 MPN/g. Results of this research provide useful information on biosafety of E. coli O157:H7 in raw milk marketed in Malaysia.